A strategy for decoupling of nonlinear systems using the inverse sub-structuring method and the parametric modal identification technique. (June 2020) - Wang, Pengtao; Wang, Jun; Lim, Teik C; Lu, Lixin; Pan, Liao
Highlights: A strategy for FRF decoupling of nonlinear system is proposed. A new nonlinear decoupling method was proposed using only system FRFs. Two numerical case studies and a FEA case study are presented for the verification. Abstract: The inverse sub-structuring method has been proposed and further developed for multi-component systems to predict the component-level frequency response functions (FRFs) only by the system-level FRFs. The previous methods are all based on the assumption that the system is linear. However, nonlinear systems are more common in engineering practices. This study aims to extend the linear inverse sub-structuring method for nonlinear systems, which can be applied to predict the FRFs of nonlinear substructure only from the system-level FRFs of the coupled nonlinear system. The formulations for nonlinear systems whose nonlinearity is previously known and only displacement-dependent is derived and verified by both lumped parameter models and FEA study. It should be noted that the nonlinear systems with known nonlinearity type and its location, and the nonlinearity can be modeled as a single nonlinear element between two coordinates. The results of the predicted nonlinear FRFs for the component are compared with those directly by measured, showing good agreement. The suggested new nonlinear inverse sub-structuring method is helpful for nonlinear component dynamics identification and/or nonlinear system vibration control.